1987
DOI: 10.1159/000116170
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Decarboxylase and Levels of Dopa and 3-O-Methyldopa: A Comparative Study of Benserazide versus Carbidopa in Rodents and of Madopar Standard versus Madopar HBS in Volunteers

Abstract: The combinations of benserazide and levodopa (1:4, Madopar®) and of carbidopa and levodopa (1:10 and 1:4, Sinemet®) are currently the most effective treatment of Parkinson’s disease. In the present comparative study some effects of the peripheral aromatic L-amino acid decarboxylase (AADC) inhibitors benserazide and carbidopa administered alone or in combination with levodopa by the oral route were investigated in two animal species (rat and mouse) and in healthy volunteers. Benserazide is about 10 times more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…An additional mechanism by which 3-OMDOPA has been suggested to interfere with the action of L-DOPA is that concerning the competition between the two compounds for AAAD (Reilly et al, 1980 (DaPrada et al, 1987) to produce an almost complete inhibition of the enzyme in peripheral tissues; the finding that no formation of dopamine was observed in renal tubules incubated with L-DOPA agrees with the view that this dose of benserazide is effective in inhibiting renal AAAD. Thus, in spite of the structural similarities between benserazide and L-DOPA or 3-OMDOPA, it might be suggested that the AAAD inhibitor does not interfere with the cell inward transport of these compounds.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…An additional mechanism by which 3-OMDOPA has been suggested to interfere with the action of L-DOPA is that concerning the competition between the two compounds for AAAD (Reilly et al, 1980 (DaPrada et al, 1987) to produce an almost complete inhibition of the enzyme in peripheral tissues; the finding that no formation of dopamine was observed in renal tubules incubated with L-DOPA agrees with the view that this dose of benserazide is effective in inhibiting renal AAAD. Thus, in spite of the structural similarities between benserazide and L-DOPA or 3-OMDOPA, it might be suggested that the AAAD inhibitor does not interfere with the cell inward transport of these compounds.…”
Section: Discussionsupporting
confidence: 57%
“…Instituto Gulbenkian de Ciencia, Oeiras, Portugal), aged 45-60 days, given benserazide (10 mg kg-', i.p.) 60 min before they were killed, in order to inhibit peripheral AAAD (DaPrada et al, 1987). In some experiments, the uptake of 3-OMDOPA was performed in renal tubules obtained from rats given saline (0.9% NaCl), instead of benserazide, 60 min before they were killed.…”
Section: Methodsmentioning
confidence: 99%
“…Since high doses of benserazide may result in inhibition of brain AADC [19], it was decided to treat rats orally with 3 mg/ kg benserazide, a dose that previously has been shown to produce maximal inhibition of liver and kidney AADC, being devoid of effects upon brain AADC [18]. In order to respect the proportion of L-DOPA/benserazide used in parkinsonian patients (4:1 ratio), the oral dose of L-DOPA used was set at 12 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Positron emission tomography studies with F-18-DOPA suggest dimin ished brain L-DOPA uptake after cocaine abuse (Bax ter et al 1988). Thus although administration of L-DOPA with decarboxylase inhibitors results in plasma L-DOPA levels many times greater than those which occur under physiologic conditions (Zurcher and Da Prada 1979;Da Prada 1984;Da Prada et al 1987), brain uptake of L-DOPA may remain a limiting factor.…”
Section: Discussionmentioning
confidence: 99%